Direct observation of the dynamic evolution of precipitates in aluminium alloy 7021 at high strain rates via high energy synchrotron X-rays. (15th February 2021) - Mirihanage, W.U.; Robson, J.D.; Mishra, S.; Hidalgo-Manrique, P.; da Fonseca, J. Quinta; Daniel, C.S.; Prangnell, P.B.; Michalik, S.; Magdysyuk, O.V.; Connolley, T.; Drakopoulos, M.
Abstract: An improved understanding of the phenomenon of dynamic precipitation is important to accurately model and simulate many industrial manufacturing processes with high strength Al-alloys. Dynamic ageing in 7xxx Al-alloys can occur as a result of both the strain and heat. Small angle X-ray scattering (SAXS) is an advanced technique that allows the precipitation processes to be studied in situ, but to date this has only been possible at lower than industrially relevant strain rates (e.g. < 10 −3 ). In this contribution, we demonstrate the potential of in-situ SAXS studies of metallic alloys at higher strain rates (10 −2 ) than previously, using a high energy synchrotron X-ray. The time resolved SAXS information has been used to evaluate dynamic precipitate evolution models and has demonstrated that at high strain rates a new regime must be considered which includes the more significant effect of vacancy annihilation, leading to a clear strain rate, rather than just strain, kinetic dependence. Graphical abstract: Image, graphical abstract